2023
DOI: 10.1039/d3sc02647g
|View full text |Cite
|
Sign up to set email alerts
|

Guiding catalytic CO2 reduction to ethanol with copper grain boundaries

Abstract: The grain boundaries (GBs) in copper (Cu) electrocatalysts have been suggested as active sites for CO2 electroreduction to ethanol. Nevertheless, the mechanisms are still elusive. This paper describes how GBs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Other experimental results also suggest that Cu grain boundaries have a positive effect on the production of C 2 + oxygenates, particularly ethanol. Using joint firstprinciples calculations and experiments, Cheng et al [94] found that the undercoordinated sites with relatively longer CuÀ Cu bond lengths on grain boundaries have a strong impact on the binding strength of bidentate adsorbates, such as *COOH and *CHO. These conditions are conducive to the initial activation of CO 2 and further CO reduction, respectively.…”
Section: Morphological Evolutions Of Co2rr Electrocatalysts Using In/...mentioning
confidence: 99%
“…Other experimental results also suggest that Cu grain boundaries have a positive effect on the production of C 2 + oxygenates, particularly ethanol. Using joint firstprinciples calculations and experiments, Cheng et al [94] found that the undercoordinated sites with relatively longer CuÀ Cu bond lengths on grain boundaries have a strong impact on the binding strength of bidentate adsorbates, such as *COOH and *CHO. These conditions are conducive to the initial activation of CO 2 and further CO reduction, respectively.…”
Section: Morphological Evolutions Of Co2rr Electrocatalysts Using In/...mentioning
confidence: 99%
“…The low ∑ values were chosen for construction, because low ∑ boundaries tended to have lower energies than average 54 . We acknowledge the existence of various grain boundary types, and modeling all types of grain boundaries is not feasible 55 .…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…6a). [127][128][129][130] Therefore, it is widely accepted that grain boundaries play a crucial role in modulating the absorption energy barriers of intermediates, thereby promoting the formation of multi-carbon products. 57,[131][132][133][134] Grain boundaries typically form between different crystalline phases of copper with the same valence state.…”
Section: Grain Boundary Effectmentioning
confidence: 99%